Tata Ruang Kantor : Kunci Efektivitas Kerja Pegawai Dapensos Bandung, Jawa Barat - Mohamad Raditya Firmana; Rabbani Raditya Gunawan (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
The effectiveness of employee performance in an organization is greatly influenced by various factors, including office layout. This research aims to analyze the influence of office layout on employee work effectiveness at the Dapenpos office in Bandung, West Java. The concept of effectiveness in this context includes the relationship between the output produced by employees and the goals or targets set by the organization. The research method used is participatory observation in the workplace to understand the interaction between office layout and employee behavior and performance. The observation results show that there are several aspects of office layout that influence the effectiveness of employee performance. One of them is room lighting, where rooms that are poorly lit tend to create a less enthusiastic atmosphere and affect employee concentration. Room temperature also plays an important role in creating work comfort, where temperatures that are too hot or too cold can interfere with employee focus and productivity. The layout of the room also has an impact, especially in terms of efficiency of interaction between work units and superiors. Apart from that, office equipment is also an important factor in supporting work effectiveness. Adequate office equipment, such as tables, chairs, laptops and photocopiers, can increase employee comfort and efficiency in carrying out their duties. Based on data from observations and interviews, the office layout conditions at Dapenpos Bandung are considered good by employees. However, there are still several rooms that require improvement, such as improving lighting and more effective room arrangement. In conclusion, good office layout can have a positive impact on the effectiveness of employee performance, increasing comfort, focus and productivity at work. This conclusion underlines the important role of office layout in creating a conducive work environment for employees. With proper attention to factors such as lighting, room temperature, room layout, and office facilities, organizations can increase the effectiveness of employee performance and achieve their business goals more efficiently.